Biotechnological applications of occlusion bodies of Baculoviruses - Lopez, Maria Gabriela; Diez, Michay; Alfonso, Victoria; Taboga, Oscar Alberto (Springer, 2019)
The ability of Baculoviruses to hyper-express very late genes as polyhedrin, the major component of occlusion bodies (OBs) or polyhedra, has allowed the evolution of a system of great utility for biotechnology. The main function of polyhedra in nature is to protect Baculovirus in the environment. The possibility of incorporating foreign proteins into the crystal by fusing them to polyhedrin (POLH) opened novel potential biotechnological uses. In this review, we summarize different applications of Baculovirus chimeric OBs. Basically, the improvement of protein expression and purification with POLH as a fusion partner; the use of recombinant polyhedra as immunogens and antigens, and the incorporation of proteins into polyhedra to improve Baculoviruses as bioinsecticides. The results obtained in each area and the future trends in these topics are also discussed.